The catalytic asymmetric synthesis of CF3-containing spiro-oxindole–pyrrolidine–pyrazolone compounds through squaramide-catalyzed 1, 3-dipolar cycloaddition. Issue 22 (22nd May 2019) - Wang, Cui; Wen, Dongwa; Chen, Hui; Deng, Yabo; Liu, Xueting; Liu, Xin; Wang, Li; Gao, Fengyun; Guo, Yifei; Sun, Mengmeng; Wang, Kairong; Yan, Wenjin
Abstract : Pharmaceutically important compounds were synthesized through the organocatalytic 1, 3-dipolar cycloaddition reaction. Abstract : Pharmaceutically important compounds were synthesized through the organocatalytic 1, 3-dipolar cycloaddition reaction. In the presence of a cinchonine-derived squaramide catalyst, the cycloaddition of N -2, 2, 2-trifluoroethylisatin ketimines with α, β-unsaturated pyrazolones gave a spiro-pyrrolidine-linked oxindole and pyrazolone compound bearing four consecutive stereocenters and two vicinal spiroquaternary chiral centers, in excellent yields and stereoselectivities.